Hippocampal and trigeminal nerve volume predict outcome of surgical treatment for trigeminal neuralgia. (May 2020) - Danyluk, Hayden; Lee, Esther Kyungsu; Wong, Scott; Sajida, Samiha; Broad, Robert; Wheatley, Matt; Elliott, Cameron; Sankar, Tejas
Background: Many medically-refractory trigeminal neuralgia patients are non-responders to surgical treatment. Few studies have explored how trigeminal nerve characteristics relate to surgical outcome, and none have investigated the relationship between subcortical brain structure and treatment outcomes. Methods: We retrospectively studied trigeminal neuralgia patients undergoing surgical treatment with microvascular decompression. Preoperative magnetic resonance imaging was used for manual tracing of trigeminal nerves and automated segmentation of hippocampus, amygdala, and thalamus. Nerve and subcortical structure volumes were compared between responders and non-responders and assessed for ability to predict postoperative pain outcome. Results: In all, 359 trigeminal neuralgia patients treated surgically from 2005–2018 were identified. A total of 34 patients met the inclusion criteria (32 with classic and two with idiopathic trigeminal neuralgia). Across all patients, thalamus volume was reduced ipsilateral compared to contralateral to the side of pain. Between responders and non-responders, non-responders exhibited larger contralateral trigeminal nerve volume, and larger ipsilateral and contralateral hippocampus volume. Through receiver-operator characteristic curve analyses, contralateral hippocampus volume correctly classified treatment outcome in 82% of cases (91% sensitive, 78% specific, p = 0.008), and contralateral nerve volume correctly classified 81% of cases (91% sensitive, 75% specific, p < 0.001). Binomial logistic regression analysis showed that contralateral hippocampus and contralateral nerve volumes together classified outcome with 84% accuracy (Nagelkerke R 2 = 65.1). Conclusion: Preoperative hippocampal and trigeminal nerve volume, measured on standard clinical magnetic resonance images, may predict early non-response to surgical treatment for trigeminal neuralgia. Treatment resistance in medically refractory trigeminal neuralgia may depend on the structural features of both the trigeminal nerve and structures involved in limbic components of chronic pain.